Neuromyelitis Optica: A Case Report - Wei-Chia Chia; Jian-Nan Wang; Ming-Chi Lai (Pediatrics and Neonatology)
Neuromyelitis optica (NMO, Devic's syndrome) is a demyelinating disease of the central nervous system that predominantly affects the spinal cord and optic nerves. It is often confused with multiple sclerosis. Early discrimination between NMO and multiple sclerosis is important because the two diseases have different natural histories and treatment regimens. Seropositivity for NMO-IgG and longitudinally extensive spinal cord lesions (3 or more spinal segments) are characteristic of NMO. Despite the absence of a definitive therapeutic strategy for NMO syndrome, methylprednisolone pulse therapy is recommended in the acute phase. Treatment strategies in relapse phases are aimed at preventing relapses, and increasing evidence shows a better clinical response of immunosuppressive therapy than immuno-modulating therapy (a standard multiple sclerosis-modulating therapy). We describe a 10-year-old girl who had visual loss due to acute optic neuritis at 6 years old and suffered repetitive myelitis 2 years later. NMO was diagnosed because of characteristic longitudinal myelitis and positive NMO-IgG. After combining therapy with prednisolone and an immunosuppressant (cyclophosphamide), the patient's medical condition was stable and no relapse symptoms were observed.